Implementation of Knowledge Management for Business Competitiveness in Provecta Capital (Venture Capital) - Fahroni, Ramdhan; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2013)
Provecta capital as new venture capital firm is facing business challenges. The firm has an obligation to promote business start-up that became the investee company. Provecta Capital business success is depends on the success of their investee companies business. Therefore, increasing business competitiveness of their investee-companies is become challenge to Provecta Capital. The development solution of Provecta Capital is by implementing knowledge management in their business. Ideally, knowledge management implementation should increase the business competiveness of investee companies. Â The research in this final project is using qualitative research by using in-depth semi structured interviews. Based on interview result, the current condition will be correlated with the basic theory of knowledge management at literature review to propose design KM strategy in Provecta Capital. After synthesizing the result, the research will elaborate on proposed design plan of knowledge management. The design plan will connect to the implementation plan of knowledge management in Provecta Capital and investee-company. Â Keywords: business competitiveness, knowledge management, venture capital.Â